ANALYSIS OF FINANCIAL PERFORMANCE USING ECONOMIC VALUE ADDED (EVA), MARKET VALUE ADDED (MVA), AND FINANCIAL VALUE ADDED (FVA) METHODS IN PT. MAYORA INDAH, TBK PERIOD 2019 – 2021 - Bani Zamzami (Asosiasi Dosen Muda Indonesia, 2023)
Financial performance reflects the company's ability to manage its financial soundness level during a certain period. The purpose of this study is to determine the measurement of the financial performance of PT Mayora Indah Tbk for the 2019 – 2021 period using the Economic Value Added (EVA), Market Value Added (MVA), and Financial Value Added (FVA) methods. Data collection techniques used, namely the study of literature and study of documentation. The type of data used is secondary data sourced from the Indonesia Stock Exchange website and the company's official website. The results of the study show that the financial performance of PT Mayora Indah Tbk for the 2019 – 2021 period using the EVA method has a positive value (EVA > 0), which means that the company's management has succeeded in creating economic added value for the company. Then the MVA method also has a positive value (MVA > 0), which means the company is able to increase the value of the capital invested by the funder. As well as the FVA method, it also has a positive value (MVA > 0), which means that the company has succeeded in providing financial added value. The creation of more financial value when the company's net profit is able to cover the equivalent depreciation (ED).